Serum matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 expression in patients with familial Mediterranean fever - Dinç, Mustafa; Tanoğlu, Alpaslan; Yazgan, Yusuf; Beyazıt, Yavuz; Öncü, Kemal; Önem, Yalçın; Hıra, Serdar; Kaplan, Mustafa; Küçük, İrfan and Sakın, Yusuf Serdar and et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Serum matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) are well-known inflammatory biomarkers, with a diagnostic potential for various diseases. The aim of the present study was to determine the potential diagnostic applications of serum MMP-9 and TIMP-1 concentrations in patients with familial Mediterranean fever (FMF). Materials and Methods: A total of 66 male FMF patients and 40 age-matched healthy subjects were included in this research. TIMP-1 and MMP-9 levels with conventional inflammation markers were determined. Pearson correlation analysis was used to determine the correlation between the characteristics of patients and the laboratory data. Results: In patients with FMF, serum MMP-9 levels and MMP-9/TIMP-1 ratios were found to be significantly elevated in both acute episode and asymptomatic periods (p=0.0001 and p=0.0001, respectively). There was no significant difference between TIMP-1 levels. A significant negative correlation between patients’ current age and TIMP-1 level in patients with acute episodes was detected (p=0.0008, r=−0.52). Moreover, a moderate negative correlation was noticed between erythrocyte sedimentation rate and TIMP-1 level in patients with acute episodes (p=0.01, r=−0.39). Additionally, a moderate negative correlation was found between the duration of colchicine use and MMP-9 and TIMP-1 levels during the attack period (p=0.04, r=−0.36 and p=0.02, r=−0.39, respectively). Conclusion: Our findings demonstrate that a significant MMP-9/TIMP-1 imbalance exists in patients with FMF, which reflects an ongoing inflammation in both FMF periods. Thus, the increased MMP-9 levels observed in FMF patients could rationalize therapeutic targeting to MMPs.